IMPLEMENTASI AUGMENTED REALITY PADA MEDIA PROMOSI PENJUALAN RUMAH - Putra, Putu Bagus Adidyana Anugrah (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2020)
The development of the industry in Indonesia has been very broad until now, it can be seen from the varied types of products produced by the company. The level of competition in product sales at companies is increasing. Increased competition in product sales can be seen from the number of exhibition events that aim to increase product sales of each company. However, the sales technique is still classified as traditional and has shortcomings in marketing, especially for marketing housing promotions that exist today. Therefore, with the rapid development of technology at this time, the real form of the house promoted by the company can be helped by using Augmented Reality technology, which will help the buyer to get a clear and clear picture of the shape and condition of the house in 3D. The development of this application uses the waterfall method with stages, (1) Requirement Analysis, (2) System Design, (3) Implementation, (4) Integration and testing and (5) Operation & Maintenance. This research resulted in an application that uses Augmented Reality technology aimed at companies in order to facilitate housing marketing where buyers can clearly see the original picture of the house being promoted in 3D